Mechanisms of Self-Concept Coherence in Late Adolescence Under Academic Pressure - Louzada Júnior, Martha; Dos Santos Lino, Jacinto (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to explore and conceptualize the psychological and contextual mechanisms through which late adolescents maintain a coherent self-concept while navigating intense academic demands in the Brazilian educational context. Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 18 late adolescents (10 females and 8 males, aged 17–21) from Brazil who were experiencing significant academic pressure. Participants were recruited through purposive sampling to ensure diversity in gender, academic stage, and performance levels. Data collection continued until theoretical saturation was reached. All interviews were conducted in Portuguese, lasted between 60 and 90 minutes, and were audio-recorded and transcribed verbatim. Thematic analysis was applied with support from NVivo software version 14, following iterative coding, category refinement, and constant comparison to ensure depth and consistency. Credibility was enhanced through peer debriefing and member checking. Findings: Four overarching thematic categories were identified: navigating academic pressure, identity negotiation and self-concept alignment, psychological adaptation strategies, and future orientation with self-continuity. Adolescents reported internalizing family and cultural expectations while simultaneously striving for authenticity, often reframing success to protect identity stability. Cognitive reframing, emotional regulation, and self-compassion emerged as key strategies to mitigate stress and preserve self-concept clarity. Social support from peers and family played a dual role, sometimes buffering stress but occasionally intensifying pressure. Future-oriented thinking, including goal reappraisal and constructing life narratives linking past, present, and envisioned adult selves, contributed to resilience and a coherent sense of self despite academic adversity. Conclusion: Maintaining self-concept coherence in late adolescence is a dynamic, context-sensitive process involving adaptive psychological strategies and relational negotiation. These insights provide a foundation for designing culturally responsive educational and mental health interventions to help adolescents sustain identity stability under academic stress.